Social Structure, Social Learning, and the Severity of Physical Intimate Partner Violence Against Women in Nigeria - Dim, Emeka Eugene (Journal of interpersonal violence, 2021)
Using the Nigerian Demographic and Health Survey (NDHS) of 2013, this study applies the social structure (feminist) and social learning perspective in understanding the severity of physical intimate partner violence (IPV) in Nigeria. About 26,403 married women were analyzed from the 2013 NDHS data. Multinomial regression was used to analyze variables that capture the social structural and social learning perspectives in relation to women’s experience of minor and severe physical IPV. The study revealed that primary and secondary educational attainment, and being employed predicted severe physical IPV victimization. Alcohol consumption by the respondents’ spouses, being a victim of childhood abuse, and witnessing IPV between parents predicted severe physical IPV. The finding of this study implies that experiences of IPV take place within a sociocultural context that shapes the social realities of the average Nigerian woman.